2019
DOI: 10.1080/13880209.2019.1660383
|View full text |Cite
|
Sign up to set email alerts
|

ShenQi FuZheng injection as an adjunctive treatment to chemotherapy in breast cancer patients: a meta-analysis

Abstract: Context: Shenqi FuZheng injection (SFI) has been suggested as a complementary treatment of chemotherapy in China. However, little is known about it in western countries.Objective: This study assesses the clinical effect of SFI combined with chemotherapy for breast cancer patients.Materials and methods: Both English and Chinese databases were searched covering the time period of 1999– 2018 for relevant studies comparing the effect of SFI plus chemotherapy treatment with chemotherapy alone in patients with breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…The purpose of this study was to demonstrate whether SQFZ improved chemotherapeutic resistance induced by cisplatin through the PI3K signalling pathway in drug-resistant breast cancer. SQFZ improves clinical efficacy, inhibits immunosuppression, and reduces toxicity in combination with chemotherapy drugs for breast cancer [ 26 , 27 ]. In the present study, we investigated the anticancer mechanisms of SQFZ action, particularly the signalling pathways involved in the reversal of drug resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of this study was to demonstrate whether SQFZ improved chemotherapeutic resistance induced by cisplatin through the PI3K signalling pathway in drug-resistant breast cancer. SQFZ improves clinical efficacy, inhibits immunosuppression, and reduces toxicity in combination with chemotherapy drugs for breast cancer [ 26 , 27 ]. In the present study, we investigated the anticancer mechanisms of SQFZ action, particularly the signalling pathways involved in the reversal of drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have demonstrated the efficacy of SQFZ combined with chemotherapy in sensitizing tumour cells and lowering toxicity [ 24 ]. SQFZ can also reduce the side effects of chemotherapy and improve the quality of life of patients with cancer [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…SQFZ is concocted from Radix Astragali (Chinese name: Huangqi) and Radix Codonopsis (Chinese name: Dangshen), and is clinically suggested as a complementary treatment of chemotherapy, and clinical practices suggest that SQFZ has therapeutic effects on cardiovascular diseases ( 75 , 76 ). Intensive researches reported that SQFZ exerts protective through improving myocardial energy metabolism, inhibiting cell adhesion and inflammatory reaction, and reducing myocardial apoptosis and avoiding ventricular remodel ( 77 ).…”
Section: Discussionmentioning
confidence: 99%
“…SM, a commonly used CPMs for treating cardiovascular diseases in the clinic, consists of extractions from Red Ginseng (Chinese name: Hongshen) and Radix Ophiopogonis (Chinese name: Maidong) (58,59). It was widely used in cardiovascular diseases and has a certain synergistic effect when combined with (75,76). Intensive researches reported that SQFZ exerts protective through improving myocardial energy metabolism, inhibiting cell adhesion and inflammatory reaction, and reducing myocardial apoptosis and avoiding ventricular remodel (77).…”
Section: The Network Pharmacology Analysis Of Cpms Against Aicmentioning
confidence: 99%
“…At present, traditional Chinese medicine (TCM) has become a common method for clinical treatment of NSCLC [5] . Some studies have confirmed that the combination of Chinese medicine and chemotherapy can improve the clinical treatment effect, achieve the effect of increasing efficiency and reducing toxicity, significantly reduce the adverse reactions caused by chemotherapy, improve the tolerance of chemotherapy, and improve the quality of life of patients [6–8] …”
Section: Introductionmentioning
confidence: 99%